Remittance-Driven Urbanization and Institutional Disconnect: Evidence from Dang District, Nepal - KC, Bikram Babu; Yadav, Himanshu (NPRC Journal of Multidisciplinary Research, 2026)
Context: Remittances account for 26.2% of the Nepalese GDP but little is known regarding their effects on secondary cities and institutional strength. The case study of Dang District showcases the trend of rapid urbanization driven by remittances in areas of poor governance.Objectives: Investigate the manner in which remittance trends affect physical and socioeconomic aspects of urbanization in secondary cities; analyze disconnects in institutional management and policy alignment in urban settings.Methodology: Secondary data synthesis of ethnographic data (2021–2023); municipal data (2005–2023); satellite images (2005, 2023); national data and policies, thematic analysis of 12 wards within Ghorahi and Tulsipur Municipalities.Results: The built-up area of Ghorahi increased from 2.8 km² (2005) to 8.6 km² (2023), marking an increase of more than 200%, while land prices were 600–800% higher. About 84% of residential growth was informal. There was low coverage of services: piped water (68%), sewerage system (35%), and solid waste collection (52%). Four disconnections in institutions were found: planning–practice, service provision, governance, and socio-spatial.Conclusion: Rapid informal urbanization fueled by remittances outpaces municipal institutional capacity. To overcome disconnect, investments in migration should be incorporated into official planning procedures and services provided in alignment with actual growth.